Denture Stomatitis in an Edentulous Iraqi Patients (Mustansiria Dental Journal, 2018)
Denture related stomatitis is an inflammatory process that mainly involves thepalatal mucosa when it is covered by complete or partial dentures; it appears frequentamong denture wearer and varies widely. Fifty patients were examined in this study,66% of them had denture stomatitis. This study aimed to evaluate the presence ofdenture stomatitis in denture wearers' patients, and to know the relation betweendenture age, denture hygiene, and denture cleansing with denture stomatitis.Results of the present study showed that poor denture hygiene was associated withhigh percentage of denture stomatitis.Also low percent of denture stomatitis appeared in the denture wearers of 3-4times/ day denture cleansing.The percentage of reduction in the prevalence of denture stomatitis was clear innewly or less years wearing dentures.